Laudato Sí: Making the Connections - Sandie Cornish (Asian Horizons, 2015)
Laudato Sí is an important and timely teaching document with great relevance for the peoples of Asia. Pastoral agents in the local churches of Asia need to understand this teaching in order to play their part in making it known, and interpreting its implications for local faith communities. This paper provides hermeneutic keys to assist pastoral workers to understand the encyclical and its place within the corpus of Catholic Social Teaching. It examines the context in which the encyclical was issued, its purpose and audience, the teaching authority that it holds, its methodology and main concerns, and its contribution to the body of CST. These reflections are intended to better equip pastoral workers in Asia to engage more deeply with the meaning and implications of the encyclical for the thinking and action of local churches. Through such engagement, they may be able to make contextualized contributions to the ongoing development of the local and universal social teachings.